The Rumpelstiltskin problem - Vande Velde, Vivian (Boston : Houghton Mifflin Harcourt, 2000)
A collection of variations on the familiar story of a boastful miller and the daughter he claims can spin straw into gold.
Bulletin (Center for Children's books)
Pub Weekly
School Library Journal
Book Report, June 2001
Bulletin (Center for Children's books), February 2001
Kirkus Review, October 2000
Keywords: Fairy tales; Folklore; Fairy tales; Folklore; Fairy tales; Folklore; Fairy tales; Folklore